Virtual-reality-enhanced mannequin to train emergency physicians to examine dizzy patients using the HINTS method - Ursat, Guillaume; Corda, Morgane; Ryard, Julien; Guillet, Christophe; Guigou, Caroline; Tissier, Cindy; Bozorg Grayeli, Alexis (Frontiers in Neurology, 2024)
Introduction Acute vertigo is a frequent chief complaint in the emergency departments, and its efficient management requires thorough training. The HINTS protocol is a valid method to screen patients in the emergency room, but its application in routine is hindered by the lack of training. This study aimed to evaluate the training of emergency physicians for the HINTS method based on a mannequin-based virtual reality simulator (MBVRS). Methods We conducted a monocenter, prospective, longitudinal, and randomized cohort study in an Emergency Department at a regional university hospital. We included 34 emergency physicians randomized into two equal groups matched by age and professional experience. The control group attended a theoretical lesson with video demonstrations and the test group received a simulation-based training in addition to the lecture. Results We showed that the test group had a higher diagnosis performance for the HINTS method compared to the control group as evaluated by the simulator at 1 month (89% sensitivity versus 45, and 100% specificity versus 86% respectively, p < 001, Fisher’s exact test). Evaluation at 6 months showed a similar advantage to the test group. Discussion The MBVRS is a useful pedagogic tool for the HINTS protocol in the emergency department. The advantage of a unique training session can be measured up to 6 months after the lesson.